Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s12098-017-2598-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal and Infantile Markers of Cobalamin Status During the First Month Post-Delivery

Abstract: Maternal cbl status is an important determinant of infantile cbl status. Both maternal holoTC and tHcy may assist in predicting infantile cbl status. The finding of high prevalence of maternal and infantile cbl deficiency in this study points towards the need for effective strategies to prevent cbl deficiency in women prior to getting pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…In one study in Germany, maternal serum vitamin B 12 and holotranscobalamin (holoTC) concentrations at delivery were significantly correlated with cord blood holoTC concentrations ( p < 0.05) [18]. In contrast, findings from cross-sectional studies examining the associations between maternal and infant vitamin B 12 concentrations later in the postpartum period have been heterogeneous [35,36,37,38,39,40]. Maternal vitamin B 12 and holoTC concentrations were significantly correlated with infant vitamin B 12 concentrations in the first month (i.e., 2–30 days) postpartum in a study in Turkey [38].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study in Germany, maternal serum vitamin B 12 and holotranscobalamin (holoTC) concentrations at delivery were significantly correlated with cord blood holoTC concentrations ( p < 0.05) [18]. In contrast, findings from cross-sectional studies examining the associations between maternal and infant vitamin B 12 concentrations later in the postpartum period have been heterogeneous [35,36,37,38,39,40]. Maternal vitamin B 12 and holoTC concentrations were significantly correlated with infant vitamin B 12 concentrations in the first month (i.e., 2–30 days) postpartum in a study in Turkey [38].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, findings from cross-sectional studies examining the associations between maternal and infant vitamin B 12 concentrations later in the postpartum period have been heterogeneous [35,36,37,38,39,40]. Maternal vitamin B 12 and holoTC concentrations were significantly correlated with infant vitamin B 12 concentrations in the first month (i.e., 2–30 days) postpartum in a study in Turkey [38]. In analyses in mother–infant dyads in the first 6 months postpartum, maternal and infant vitamin B 12 concentrations were significantly associated in Canada and Cambodia (i.e., 3–27 weeks) [37], but not in India (i.e., 1–6 months) [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted in Turkey reported that the rates of maternal and infantile vitamin B12 deficiency were 76.7% and 60.8% during the first month post-delivery, respectively. 1 On the other hand, although vitamin B12 deficiency has been reported extensively, the clinical spectrum of abnormal movements due to infantile B12 deficiency has been shown to be remarkably wide. 9,10 ITS is characterized by paleness, growth retardation, tremor, hyperpigmentation, movement disorders, and sparse brown hair.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetarian diet, pernicious anemia, and low socioeconomic level are common etiological factors associated with vitamin B12 deficiency in breastfeeding mothers and their children. 1 Vitamin B12 begins accumulating in the infant within the first six months after birth while mothers often remain asymptomatic and the deficiency in the infant may not be noticed until the onset of neurological effects. 2 Infantile symptoms including restlessness, nutritional problems, and neuromotor growth retardation become pronounced over time.…”
mentioning
confidence: 99%